Efektivitas Hukum Humaniter Internasional Dalam Kejahatan Perang Pada Konflik Suriah - Annisa Diva Sekartaji; Fatiha Firdaus; Istiqomah Istiqomah; Ida Susilowati (JOURNAL of LEGAL RESEARCH, 2021)
International Humanitarian Law regulates war in two broad categories: international armed conflict (IAC) and non-international armed conflict (NIAC). The conflict in Syria is an example of a war that has claimed numerous lives. A non-international armed conflict is what it is called when it comes to the crisis in Syria. Violence, both physical and mental, began to take place in Syria. In the aftermath of the political upheaval, a civil war broke out, resulting in war crimes such as murder, kidnapping, bombardment, and rape. The bloodshed and the worst humanitarian disaster in Syria's history were a direct result of this. " The goal of this investigation was to determine the efficiency of International Humanitarian Law in dealing with the war crimes committed in Syria. A deductive approach to descriptive qualitative research was used in this study. Furthermore, the information used in this study was culled from reputable sources such as academic publications and news websites. Since there were so many violations of international humanitarian law during the Syrian crisis, it's hard to tell how effective it was in helping to end the conflict.